A dictionary of ancient Near Eastern architecture - Leick, Gwendolyn, 1951- (Routledge, 1988)
This Dictionary gives a comprehensive survey of the whole range of ancient Near Eastern architecture from the Neolithic round huts in Palestine to the giant temples of Ptolemaic Egypt. Gwendolyn Leick examines the development of the principal styles of ancient architecture within their geographical and historical context, and describes features of major sites such as Ur, Nineveh and Babylon, as well as many of the lesser-known sites. She also covers the variations of typical ancient architectural structures such as pyramids, tombs and houses, details the building material and techniques employed, and clarifies specialist terminology.